Lady Macbeth Breaks the Mould: Reconstruction of the Female Identity in Zinnie Harris’s Macbeth (an undoing) - Esra Ünlü Çimen (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Zinnie Harris (1972 -) is a prominent contemporary British playwright known for her original plays and rewritings of renowned Western male playwrights’ works. In her rewritings, Harris gives new stories to the popular female figures of Western drama to challenge the dominant strand of criticism about the original plays, especially regarding the common reviews of these female characters often produced by male critics with gendered biases. Although her recent play, Macbeth (an undoing) (2023), is explicitly based on William Shakespeare’s Macbeth, it apparently differs from it since Harris portrays Lady Macbeth as a self-conscious character aware of her fictionality who aims to offer her version of the plot generated by Shakespeare and indicate several gaps in it. In Harris’s version, Lady Macbeth emerges as a strong-willed woman with no intention to kill herself while Macbeth appears as the one with mental disorder. Besides giving more voice to Lady Macduff, who appears in only one scene (4.2) where she and her son are killed in Macbeth, Harris’s Lady Macbeth aims to acquit the women labelled as witches in Shakespeare’s period. Within this context, this article argues that Harris’s play is a medium through which she aims to reconstruct the female identity embodied by Lady Macbeth, Lady Macduff and the witches in Macbeth and its later criticism by sexist voices. The purpose of the study is to focus on the individual stories of these female characters in Harris’s rewriting to question their conventional criticisms from a contemporary perspective offered by the playwright.